Ángel Crespo, La vida plural de Fernando Pessoa, Barcelona, Seix Barral, 2007, 414 pp. (Estudios Humanísticos. Filología, 2008)
Ángel Crespo, La vida plural de Fernando Pessoa, Barcelona, Seix Barral, 2007, 414 pp.